Evidence of zoonotic leprosy in Pará, Brazilian Amazon, and risks associated with human contact or consumption of armadillos - da Silva, Moises B., author; Portela, Juliana M., author; Li, Wei, author; Jackson, Mary, author; Gonzalez-Juarrero, Mercedes, author; Hidalgo, Andrea Sánchez, author; Belisle, John T., author; Bouth, Raquel C., author; Gobbo, Angélica R., author; Barreto, Josafá G., author; Minervino, Antonio H. H., author; Cole, Stewart T., author; et al. (Colorado State University. Libraries, 2018)
Mycobacterium leprae (M. leprae) is a human pathogen and the causative agent for leprosy, a chronic disease characterized by lesions of the skin and peripheral nerve damage. Zoonotic transmission of M. leprae to humans by nine-banded armadillos (Dasypus novemcinctus) has been shown to occur in the southern United States, mainly in Texas, Louisiana, and Florida. Nine-banded armadillos are also common in South America, and residents living in some areas in Brazil hunt and kill armadillos as a dietary source of protein. This study examines the extent of M. leprae infection in wild armadillos and whether these New World mammals may be a natural reservoir for leprosy transmission in Brazil, similar to the situation in the southern states of the U.S. The presence of the M. leprae-specific repetitive sequence RLEP was detected by PCR amplification in purified DNA extracted from armadillo spleen and liver tissue samples. A positive RLEP signal was confirmed in 62% of the armadillos (10/16), indicating high rates of infection with M. leprae. Immunohistochemistry of sections of infected armadillo spleens revealed mycobacterial DNA and cell wall constituents in situ detected by SYBR Gold and auramine/rhodamine staining techniques, respectively. The M. leprae-specific antigen, phenolic glycolipid I (PGL-I) was detected in spleen sections using a rabbit polyclonal antibody specific for PGL-I. Anti-PGL-I titers were assessed by ELISA in sera from 146 inhabitants of Belterra, a hyperendemic city located in western Pará state in Brazil. A positive anti-PGL-I titer is a known biomarker for M. leprae infection in both humans and armadillos. Individuals who consumed armadillo meat most frequently (more than once per month) showed a significantly higher anti-PGL-I titer than those who did not eat or ate less frequently than once per month. Armadillos infected with M. leprae represent a potential environmental reservoir. Consequently, people who hunt, kill, or process or eat armadillo meat are at a higher risk for infection with M. leprae from these animals.
Keywords: armadillos; leprosy; spleen; acid-fast stain; meat; Brazil; hematoxylin staining; Mycobacterium leprae